Delayed Presentation of Trichobezoar with Small Bowel Obstruction - Zamir, Naima (EL-MED-Pub, 2011)
Small bowel obstruction is a common surgical emergency but trichobezoar as an etiology, rarely reported. A seven year old school going female child presented with acute intestinal obstruction with a palpable and mobile mass in the abdomen. At exploration, a 10 cm long trichobezoar was found in the distal ileum which was removed through enterotomy. Postoperative course remained uneventful. Further probing revealed that child used to eat her own scalp hairs at the age of 2 years and the habit persisted for about 18 months which resulted in alopecia at that time. Later on she started showing normal behavior.